EVALUATION OF PRODUCTIVITY IN THE STUDY OF POULTRY BIOPHYSIOLOGY - Khoshniyazova Saulat Zhalgasbaevna; Karimov Rashid Parahatovich; Murodova Azoda Kadirbergan kyzy (Academia Science Repository, 2023)
The article discusses the assessment of the productivity of birds in Uzbekistan.